PENGELOLAAN DAN KONSUMSI GARAM BERIOIDUM RUMAH TANGGA DI DESA TANGGAHAN PEKEN KECAMATAN SUSUT KABUPATEN BANGLI - Ni Kadek Kertiani; I_Komang Agusjaya Mataram; A_A_Gde Raka Kayanaya (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2022)
iodized salt is salt that has been enriched with iodine which is needed by the body for growth. The problem in this study is how the management and consumption of iodized salt in the household in the resilient village of Peken Subdistrict, Susut, Bangli Regency. The purpose of this study was to determine the management and consumption of iodized salt in households in the resilient village of female workers in the Shrinkage District of Bangli Regency. The sample size obtained was 36 samples. The results of this study indicate that the level of iodized salt consumption in housewives is sufficient category 25 (69.45%) with less category 11 (30.55%), how to use and the level of iodized salt consumption category 36 (100%) sufficient and the storage and consumption level of iodized salt with less category is 25 (75%) but there are still enough categories of 9 (25%). The tendency of all samples that consume enough iodized salt is still using it when cooking as many as 25 samples (100%). consume iodized salt with less categories as many as 7 samples (77.8%) tendency to openly save while samples who consume iodized salt as less as 7 samples (63.7%) tendency to consume iodized salt with work. The trend of all samples consuming iodized salt is enough with high school / vocational education as many as 11 samples (44%). The tendency of samples that consume enough iodized salt are those who have weaving work / housewives, each of which is 17 (68%).Keywords: Management, Consumption, Iodium salt